REFORM OF CIVIL PROCEDURAL LAW AT THE APPELLATE-LEVEL COURTS IN INDONESIA - Mohammad Amir Hamzah (Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractThe frst court and the appellate-level court serve as the judex facti, but there are different regulations about procedural law in HIR, RBG, and Law No. 20 of 1947. It causes high fling of cassation appeals. As a result, the Supreme Court is impaired in fostering and developing the (civil) law due to it being hectic from examining cases. Through reform of civil procedure law of the appellatelevel court (PT), the court will be placed in the appropriate position as the means of fltering proceedings, so that not all cases can be fled for a cassation appeal. It is also the time to revoke Law No. 20 of 1947.IntisariPada dasarnya Pengadilan Negeri dan Pengadilan Tinggi diposisikan sebagai judex facti. Namun demikian, terdapat beberapa pengaturan mengenai hukum acara perdata mulai dari HIR, RBG hingga UU No.20 Tahun 1947 yang mengatur hal tersebut secara berbeda. Akibatnya, pengajuan kasasi meningkat sehinggamengganggu fokus Mahkamah Agung melaksanakan fungsi pembinaan hukum. Seharunya pengadilan banding diposisikan sebagai penyaring sehingga tidak semua kasus dapat diajukan ke banding dan kasasi. Selain itu, melalui pembaharuan hukum ini juga UU Nomor 20 Tahun 1947.